Rural development concepts and components - Valera, Jaime B. (1989)
The history of development concepts presents general ideas that can be applied to the discussion of rural development. The linear view of development, typified by the trickle down and modernization models, and the theory of underdevelopment, espoused in dependency theory, are discussed in this paper. From these models, the concept of rural development is introduced as a continuation and elaboration of the general idea of development. Two approaches are emphasized: one that seeks productivity; the other, using social and political processes. The basic human needs method of targetting can then be used to attain goals based on these two approaches.
Keywords: Rural development; Economic development -- Government policy